MAGNETIC RESONANCE IMAGING IN THE EVALUATION OF HYDROCEPHALUS. (International journal of medical sciences, 2025)
Hydrocephalus is a pathological condition characterized by the accumulation of excess cerebrospinal fluid in the ventricles of the brain. This disease occurs in adults and children of any age and is associated with a violation of one of the mechanisms of cerebrospinal fluid circulation. This may be due to impaired fluid reabsorption or increased fluid production. Currently, magnetic resonance imaging (MRI) is the most effective method for the early diagnosis of hydrocephalus. Hydrocephalus is one of the most common diseases with a violation of the cerebrospinal fluid of the brain, and MRI is the most convenient and effective method for diagnosing any of its stages.